Cost utility of photodynamic therapy for predominantly classic neovascular age related macular degeneration. Issue 8 (16th July 2004) - Hopley, C; Salkeld, G; Mitchell, P
Abstract : Background/aim: Age related macular degeneration (AMD) is the leading cause of severe vision impairment and blindness in older people throughout the developed world and currently affects around 420 000 UK citizens. Choroidal neovascularisation (CNV) is treatable with photodynamic therapy (PDT) but is expensive at over £1200 per treatment. The aim of this study was to assess the cost utility of PDT for better eye, predominantly classic, subfoveal choroidal neovascular lesions secondary to AMD. Methods: Cost utility analysis (CUA) was conducted to estimate the cost effectiveness of PDT for scenarios involving reasonable (6/12) and poor (6/60) visual acuity. The models incorporated data from the Treatment of Age-related Macular Degeneration with PDT (TAP) Study and patient based utilities. The incremental CUA was based on decision analytical models, comparing treatment to a placebo comparator. Extensive one way sensitivity analysis of parameters was conducted to determine the robustness of the model. A discount rate of 6% was used for costs and quality adjusted life years (QALY). Results: Model 1: in people with reasonable initial visual acuity, the cost utility of treating applicable neovascular AMD lesions was £31 607 per QALY saved, with a sensitivity analysis range from £25 285 to £37 928. Model 2: in people with poor initial visual acuity, the cost utility was £63 214 per QALY saved, with a sensitivity analysis range from £54 183 to £75 856. Conclusions: PDT treatment is the only available treatment for some forms of neovascular ("wet") AMD. Under these assumptions, PDT can be considered moderately cost effective for those with reasonable visual acuity but less cost effective for those with initial poor visual acuity. These findings have implications for ophthalmic practice and healthcare planning.